Behind Closed Doors: The Stigma of Suicide Loss Survivors. (September 2018) - Sheehan, Lindsay; Corrigan, Patrick W.; Al-Khouja, Maya A.; Lewy, Stanley A.; Major, Deborah R.; Mead, Jessica; Redmon, Megghun; Rubey, Charles T.; Weber, Stephanie
Many thousands of families lose a loved one to suicide each year. The stigma experienced by family survivors threatens to further burden families and impede the grieving process. This study used a community-based participatory research process to explore the family stigma of suicide from a social-cognitive perspective. We describe a secondary analysis of qualitative data focusing on stigma directed at bereaved families. Thematic analysis of focus group data ( n  = 62) resulted in themes describing stereotypes, prejudice, and discrimination. Bereaved families were viewed as contributing to their loved ones death through abuse, neglect, denial, or failure to provide adequate help. Bereaved families were seen as emotionally strong, victims of the suicide, or as contaminated by their association. Families encounter pressure to keep the suicide a secret and experience withdrawal of support systems. Results suggest needs for evidence-based programs to address both public and internalized stigma experienced by bereaved families.